Junho de 2013 e os avanços da Tarifa Zero: uma análise das antecedências e repercussões da luta a partir de uma crítica dos afetos - Júlia Ceccon Ortolan (2024)
This work deals with the June 2013 Uprisings in Brazil, based on the guiding thread of urban mobility – more specifically, on the mobilizations, horizons and achievements of the fight for Fare-free public transport. By understanding the revolts from the notion of an event, which takes place at the intersection between material and subjective conditions and functions as points of inflection and historical opening, the advances and repercussions linked to June are investigated. The main thesis is that the June protests contributed to the proliferation of Fare-free public transport policies in the country, given the more than one hundred municipalities that currently have the system. The relationships that are established between 2013 uprising event and advances in urban mobility do not consist of simplistic causal associations: it must be considered the multidimensionality of the event, as well as its symbolic effects, which are registered, in addition to its immanence, in the bodies, subjects and political imaginaries. To understand the repercussions of June 2013 on today's social and political imagination, it is necessary to investigate the affective dispositions and subjects involved at the time – as well as the place that these subjects and affects occupy today. From this perspective, the research follows an analytical path in the light of a critique of affections, which considers the causes for what one feels and establishes evaluation parameters within social theories. Observing parameters of social justice, this work outlines panoramas relating to urban mobility and the mobilizations of June 2013, discussing concrete and subjective aspects that allow us to think about the implications of the revolts on current forms of political subjection. With the incursion into affections, it can be seen that the June Revolts had a character of rupture in relation to the hegemonic and characteristic modes of subjectivation of Brazilian society. It also presented, among its implications, the repositioning of popular revolts at the center of the political and social dynamics, consecrating them as a sign of the political struggles of contemporary Brazilian society.